Cognitive-behavioral therapy for the improvement of negative symptoms and functioning in schizophrenia: A systematic review and meta-analysis of randomized controlled trials. - Yu Hong; Yiyun Chen; Yinglin Bai; Wenfei Tan (PLoS ONE)
Background Negative symptoms of schizophrenia are a range of deficits or losses in mental functioning associated with the disorder, including blunted affect, alogia, avolition, asociality, and anhedonia. These symptoms severely impact the quality of life of patients and hinder the recovery process. They significantly impair patients' ability to live independently, maintain social relationships, and function effectively in society. However, current treatments for negative symptoms of schizophrenia are limited in efficacy and remain controversial. Cognitive-behavioral therapy (CBT) is a goal-oriented psychotherapy that aims to improve individuals' emotional and psychological states by changing their negative thought patterns and behaviors. It helps patients identify and challenge irrational beliefs while promoting more positive behavioral changes through behavioral experiments and skills training. This study aims to conduct a meta-analysis to assess the effects of CBT on negative symptoms and function in schizophrenia. Objectives This study aimed to investigate the effects of cognitive behavioral therapy on negative symptoms, mental function, social skills, and social functioning in schizophrenia. Methods Literature was retrieved from 10 databases (PubMed, EMBASE, Cochrane Library, Web of Science, APA PsycINFO, CINAHL, MEDLINE, CNKI, Wan fang Database and SinoMed,), with the search period ranging from the inception date to 1 September 2024. Two researchers independently conducted a literature review, data extraction, and risk of bias assessment. The quality of the included studies was assessed using the Cochrane Risk of Bias tool, and the meta-analysis was conducted using RevMan 5.3. The measurement outcomes include negative symptoms of schizophrenia, overall function, social skills, and social functioning. Result The analysis included a total of 15 studies involving 1,311 participants. All studies used the Positive and Negative Syndrome Scale (PANSS) as the assessment tool for measuring negative symptoms of schizophrenia. The results of the meta-analysis indicated that cognitive-behavioral therapy (CBT) significantly improved negative symptoms in patients with schizophrenia compared to treatment as usual (TAU) (MD = -1.65, 95% CI = -2.10 to -1.21, p < 0.001, I² = 41%). Short-term CBT significantly improved negative symptoms in schizophrenia (MD = -2.71, 95% CI = -3.18 to -1.61, p < 0.001, I² = 48%). Medium-term CBT also significantly improved negative symptoms (MD = -1.80, 95% CI = -2.76 to -0.84, p < 0.001, I² = 29%). Long-term CBT demonstrated significant improvement in negative symptoms as well (MD = -1.70, 95% CI = -2.54 to -0.85, p < 0.001, I² = 0%). CBT significantly improved overall function in patients with schizophrenia (SMD = 0.38, 95% CI = 0.13 to 0.63, p < 0.05, I² = 0%). Additionally, CBT significantly enhanced social skills (SMD = 0.87, 95% CI = 0.58 to 1.16, p < 0.001, I² = 0%) and social functioning (SMD = 0.19, 95% CI = 0.03 to 0.36, p < 0.05, I² = 24%) in these patients. Conclusion The results indicate that cognitive behavioral therapy has a significant effect on improving the negative symptoms of schizophrenia and is markedly superior to Treatment as Usual (TAU). Moreover, all three sub-treatment approaches (short-term, medium-term, and long-term) can sustainably and significantly improve negative symptoms of schizophrenia. Future research should focus on developing and evaluating cognitive therapies targeting negative symptoms, providing more reliable evidence and applying these research findings to clinical practice.